PENGGUNAAN TEKNIK SURVEY, QUESTION, READ, RECITE / RECALL, REVIEW (SQ3R) TERHADAP MEMBACA PEMAHAMAN SISWA TUNARUNGU KELAS I SMPLB - NUR ALFINA, ZAHRO (Jurnal Pendidikan Khusus, 2017)
Abstract: Deafness has an impact on language skills in children. As a result little information received by children so that children have difficulty understanding the reading on the subjects of Bahasa Indonesia. This study aims to analyze the influence of SQ3R technique in learning to read children with hearing impairment class I in SMPLB-B Karya Mulia Surabaya, especially in terms of reading comprehension on learning Indonesian. This study uses a quantitative approach to research the type of pre-experiment and design of the study one group pre-test - post-test design. Subjects studied children with hearing impaired class I in SMPLB-B Karya Mulia Surabaya amounted to 7 people. Test data collection techniques such as statistical data analysis techniques with the non-parametric Wilcoxon test formula match pairs test. The results of data analysis showed that the initial test / pre-test average obtained is 54.29 and given treatment after the final test / post-test with the average obtained for 80 This suggests that there is a significant increase. The value of Zh = 2.368 is greater than the critical value of 5% Zt = 1,96 which means Ho is rejected and Ha accepted so it can be said the influence of the use of SQ3R technique on the ability to read the understanding of hearing impaired children in SMPLB-B Karya Mulia Surabaya.   Keywords: Glass analysis, beginning reading